Boosting Students’ Participation Through the Implementation of Virtual Station Rotation Model - I Made Perdana Skolastika (ELLITE, 2020)
In the amid of Covid-19 pandemic, almost all schools and other educational platforms are forced to switch the conventional learning into an online learning system. Based on several previous studies, it is found that students’ low participation is one of the major problems experienced by teachers and lecturers. In line with that, this article aims to modify traditional station rotation model into a virtual model in order to fulfill teachers’ need to accommodate and increase student participation in online learning. This article starts with an evaluation of previous research that discusses the concept and procedures to implement the traditional station rotation model in learning. The discussion leads to the potential of modifying the traditional station rotation model into the virtual model. The implementation of the virtual station rotation model in this article will emphasize the possibility of applying this model to increase student participation in online learning which is currently being carried out by almost all schools. The results of the research reviews discussed in this article show the great possibility of applying this model to online learning in order to increase student participation. Furthermore, this research can be used as a reference in applying and developing this learning model both in the implementation of classroom teaching and further research.